Optimal monetary policy during endogenous housing-market boom-bust cycles - Hajime Tomura (Bank of Canada, 2009)
This paper uses a small-open economy model for the Canadian economy to examine the optimal Taylor-type monetary policy rule that stabilizes output and inflation in an environment where endogenous boom-bust cycles in house prices can occur. The model shows that boom-bust cycles in house prices emerge when credit-constrained mortgage borrowers expect that future house prices will rise and this expectation is neither shared by savers nor realized ex-post. These boom-bust cycles replicate the stylized features of housing-market boom-bust cycles in industrialized countries. In an environment where mortgage borrowers are occasionally over-optimistic, the central bank should be less responsive to inflation, more responsive to output, and slower to adjust the nominal policy interest rate. This optimal monetary policy rule dampens endogenous boom-bust cycles in house prices, but prolongs inflation target horizons due to weak policy reactions to inflation fluctuations after fundamental shocks.
Keywords: E44; E52; 330; Credit and credit aggregates; Financial stability; Inflation targets; Konjunktur; Immobilienpreis; Geldpolitik; Gesamtwirtschaftliche Produktion; Inflationsrate; Taylor-Regel; Kleines-offenes-Land; Kanada